Development and calibration of a dynamic flotation circuit model. (October 2016) - Seppälä, Pirjo; Sorsa, Aki; Paavola, Marko; Ruuska, Jari; Remes, Antti; Kumar, Haresh; Lamberg, Pertti; Leiviskä, Kauko
Highlights: A dynamic simulator is developed for a mini-pilot scale beneficiation plant. The effects of ore type variation and pH are included in the simulator. The flotation circuit model is identified with experimental data. Quantitative validation shows good performance. The simulator can be used, for example, in process design, monitoring and as a decision support system. Abstract: Monitoring of mineral beneficiation processes is difficult due to lack of reliable measurements and hazardous environment. Therefore robust models describing steady-state and dynamic behaviour of the processes are needed when aiming for improved monitoring and control. Specific characteristics of models used in mineral processes are that they require spatial mineralogical information of raw material. In this study, a dynamic simulator combining ore characteristic physical data, process operating parameters and mineralogical properties is developed for the Oulu Mining School (OMS) mini-pilot scale mineral beneficiation plant. The mini-pilot process, theoretical part of the model and the model development are described. Open and closed flotation circuit experiments were carried out in mini-pilot research environment for model identification. Experimental and simulated results of ore type variation and pH change are presented. Based on the results the effects of the aforementioned factors on flotation performance are predicted.